Considering thickness-accommodation, nesting, grounding and deployment in design of Miura-ori based space arrays. (August 2022) - Bolanos, Diana; Ynchausti, Collin; Brown, Nathan; Pruett, Hunter; Hunter, Jared; Clark, Brooklyn; Bateman, Terri; Howell, Larry L.; Magleby, Spencer P.
Abstract: The Miura-ori pattern exhibits favorable qualities desirable for deployable space arrays — especially achieving a large deployed area from a compact stowed volume. However, implementing the Miura-ori into a finite-thickness, engineered system poses challenges that are not manifest in a zero-thickness model. As such, it is important to understand and address the limitations of the pattern before implementing it into an engineered system. This paper presents the Miura-ori as a favorable, yet challenging, pattern in design of deployable space arrays. Challenges including thickness-accommodation, nesting, grounding and deployment are presented to introduce designers to unapparent complications associated with design of Miura-ori systems. A preliminary set of approaches to address and mitigate design difficulties is then provided. Highlights: Miura-ori pattern exhibits favorable qualities needed for deployable space arrays. Multiple factors affect smooth, one-degree-of-freedom deployment. Propagation of nesting is a challenge for thick panels in the Miura-ori. Methods presented to mitigate challenges of grounding, nesting, and deployment. Examples of implementation in thick materials provided.